2010
DOI: 10.4103/0301-4738.71713
|View full text |Cite
|
Sign up to set email alerts
|

Cataract surgery under topical anesthesia using 2% lignocaine jelly and intracameral lignocaine: Is manual small incision cataract surgery comparable to clear corneal phacoemulsification?

Abstract: A prospective comparative study was undertaken to compare the patients’ pain experience, surgical outcome and surgeon’s experience in phacoemulsification and manual small incision cataract surgery (MSICS) under topical anesthesia supplemented with intracameral lignocaine (TASIL). In Group 1 (n=88) phacoemulsification was done and in Group 2 (n=92) MSICS was done. Pain scores were marked by the patients on a Visual analog scale (VAS) after the surgery. The surgical experience was noted on a questionnaire by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 7 publications
(12 reference statements)
2
18
0
Order By: Relevance
“…These results corroborate findings reported by some authors (12) , who assessed the advantages and disadvantages of topical anesthesia with intracameral lidocaine. These authors found that most patients did not exhibit any pain and that the experience was rated positive by the surgeons with respect to patient collaboration, stability of the anterior chamber, level of difficulty in the performance of phacoemulsification, and complications.…”
Section: Discussionsupporting
confidence: 92%
“…These results corroborate findings reported by some authors (12) , who assessed the advantages and disadvantages of topical anesthesia with intracameral lidocaine. These authors found that most patients did not exhibit any pain and that the experience was rated positive by the surgeons with respect to patient collaboration, stability of the anterior chamber, level of difficulty in the performance of phacoemulsification, and complications.…”
Section: Discussionsupporting
confidence: 92%
“…2 Because the surgical technique is improving, there is a general trend toward smaller incisions and less invasive maneuvers in MSICS. This has been accompanied over the last year by a renewed interest in topical anesthetic techniques, 18,19,22 which in many cases enhance the patient's comfort and reduce the inherent risks of retrobulbar and peribulbar injection. Topical anesthesia has the potential to serve as a safe, economic, and easy technique for MSICS.…”
Section: Discussionmentioning
confidence: 99%
“…13,19 In A total of 300 patients were randomly assigned into the topical anesthesia plus intracameral BSS group (placebo group) or the topical anesthesia plus intracameral lidocaine group (interventional group) according to the random numbers table. Comparisons between the 2 groups were analyzed with the Student t test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Since then, topical anesthesia has been successfully used by different authors for cataract surgery, 2Y6 trabeculectomy, 7,8 vitrectomy, 9 and phacotrabeculectomy surgery. 10,11 Recent evidence suggests that topical anesthesia with lignocaine 2% jelly instead of lignocaine 2% solution is safe and effective for manual small incision cataract surgery 12 and clear corneal cataract surgery 13,14 without systemic sedation. A literature review has shown that lignocaine jelly has a longer duration of action when compared with other topical anesthesia alternatives and is equally effective.…”
mentioning
confidence: 99%